Assisting Freshman Student-Athletes with Educational Planning and Career Development - Hattig, Sally (My University, 1991)
In many academic support centers, a primary focus is on helping student athletes adjust to the collegiate environment and the increased demands of being a student and an athlete. This paper discussed the primary issues facing student-athletes with the interrelated career development issues, a description of a freshman academic and career exploration class, the results of the Survey of Career Development, and a discussion of intervention strategies and referral agencies. As a part of the Freshman Enrichment Program at Penn State University, all freshman student-athletes were enrolled in the Academic and Career Exploration course in spring semester 1988. The analysis was conducted only on the surveys completed by an individual in both the fall and spring semesters, forming a matched sample of 127 freshman student-athletes. A gender breakdown included 62 females and 65 males. This research found significant growth in career development from the fall semester to the spring semester for freshman student-athletes enrolled in an academic and career development course. The issue of student-athletes' lack of involvement and motivation in career planning and development presents developmental concerns to academic counselors.
Keywords: career development; freshmen